Case study research : principles and practices / John Gerring. - Gerring, John, 1962- (Strategies for social inquiry., 2017)
This volume provides a general understanding of the case study method as well as specific tools for successful implementation. Topics include the definition of a 'case study', the strengths and weaknesses of this distinctive method, strategies for choosing cases, an experimental template for understanding research design, and more. Thoroughly updated, this new edition provides an understanding of the case study research method and the tools required for its implementation.